Knowledge in modern organisations: establishing the link between knowledge management, organisational learning, environmental dynamism and innovation : (a comparative study of mobile companies in Zimbabwe and South Africa) - Masoka, Tinashe (My University, 2019)
Knowledge Management has become a key fundamental asset for any organisation`s productivity gains, i.e. product or service innovation. But it does not work in isolation; aspects such as Organisational Learning have proved to be important too as organisations aim to have their employees well equipped with the internal and external environment. That being said, organisations operate in a dynamic environment that keeps changing all the time in terms of technology, financial markets, customer buying-behaviour, amongst other factors. As such, mobile organisations are innovation bound in terms of their products and services that they offer; hence, innovation is their main priority. This research study examines the link that exists between knowledge management, organisational learning, environmental dynamism towards achieving innovation amongst mobile organisations, Organisation A and Organisational B, in Zimbabwe and South Africa respectively. This research study will hypothesize and test knowledge management, organisational learning and environmental dynamism against innovation across the two organisations with a total sample of 370. The results highlight knowledge management, organisational learning and environmental dynamism as positively correlated and there is a statistical significant relationship between knowledge management, organisational learning and environmental dynamism towards innovation. The results also indicated that ED plays a moderating role in regulating how innovative organisations can be with organisations in high unstable environments having high innovation levels. The major implication that will be a limitation for this research study is that the data collected is limited to organisations in South Africa and Zimbabwe only. The practical implications for this research study will aim to contribute to management of organisations to utilise and illustrate that knowledge management, organisational learning and environmental dynamism form part of the bottom line of the organisation towards achieving innovation levels. This research study aims to contribute to the literature that exists on knowledge management, organisational learning, and environmental dynamism by empirically analysing their effects on innovation. It also highlights the interaction and link that exists between knowledge management, organisational learning and environmental dynamism and how these facets work hand in hand to attain innovation levels in organisations that will make them competitive over their rivals.
A research dissertation submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for award of the degree of Master of Commerce (Management) in the School of Economic and Business Sciences.
Keywords: Knowledge management; Organizational learning